Social equity and livelihood implications of REDD+ in rural communities – a case study from Nepal. Issue 1 (March 2015) - Poudel, Mohan; Thwaites, Rik; Race, Digby; Dahal, Ganga Ram
Despite growing international consensus that the use of the policy instrument REDD+ (Reducing Emissions from Deforestation and forest Degradation in developing countries) could be an effective way to reduce carbon emissions from the forestry sector and support bio-diversity with livelihood benefits, there are a range of unresolved issues, including potential implications for rural livelihoods. This paper presents results from recent research that examines social equity and livelihood implications of the piloting of REDD+ through Nepal's community forestry system, within selected villages in the Gorkha district of Nepal. The research reveals the varying experiences of households, closely correlated to the socio-economic attributes of the households. Despite the 'no harm and equitable' policy, this research indicates that not everyone is experiencing the anticipated benefits of REDD+. Although poorer, women-headed and marginalized households are targeted in some ways (e.g. seed grants), the support is limited, and inadequately compensates the loss they have experienced in other ways (e.g. limited access to forests). Households bundling by caste may not necessarily address equity, but is likely to increase intra-caste marginalization.